Serum Adiponectin Levels Are Positively Associated With Diabetic Peripheral Neuropathy in Chinese Patients With Type 2 Diabetes - Sun, Qing; Yan, Bin; Yang, Dan; Guo, Jie; Wang, Chao; Zhang, Qian; Shi, Yue; Shi, Xiaohu; Tian, Guoqing; Liang, Xiaochun (Frontiers in Endocrinology, 2020)
Objective: To investigate the association between serum adiponectin levels and diabetic peripheral neuropathy (DPN) in Chinese type 2 diabetes (T2D) patients. Design and Methods: A total of 219 T2D patients aged 40-79 years were divided into two groups according to whether they had DPN. The systemic levels of potential five biomarkers were measured by using a human adipokine multiplexed bead-based immunoassay. Diabetic peripheral neuropathy diagnostic criteria included both common DPN symptoms and neurological screening tests. Results: Most features of DPN and non-DPN patients are similar, but the DPN patients were slightly older, had longer diabetes duration, higher hemoglobin (Hb) A1c, lower estimated glomerular filtration rate (eGFR) levels, less exercise, and more often used lipid-lowering drugs. Serum adiponectin levels of DPN patients were higher than that of non-DPN patients (8.13 vs. 9.63 mg/ml, P = 0.004). Serum adiponectin levels were positively associated with DPN after adjustment for age, gender, body mass index, hypertension, HbA1c, alcohol intake, smoking status, physical activity, log-transformed low density lipoprotein cholesterol, the use of lipid-lowering drugs, eGFR and diabetes duration [OR 1.72 (95% CI 1.02-2.89), P = 0.041]. Conclusions: Serum adiponectin levels of DPN patients were higher compared with non DPN patients in this Chinese T2D population. Higher serum adiponectin levels might be an independent risk factor in the pathogenesis of DPN.